Job demands-resources on digital gig platforms and counterproductive work behavior - Zhao, Shanshan; Liu, Yanfeng (Frontiers in Psychology, 2024)
With the rapid expansion of digital gig platforms, counterproductive work behavior among gig workers has become increasingly prominent, adversely impacting the platform's reputation, operational efficiency, and user experience. This study, grounded in the Job demands-resources model and Job engagement theory, develops a second-order chain mediation structural model to explore how the second-order variables of job demands, comprising work pace/workload, physical demands, psychological demands, and customer-related social stressors, and job resources, comprising compensation, job security, learning opportunities, and opportunities for professional development, affect counterproductive work behavior among gig workers on digital platforms. The findings reveal that job demands positively influence counterproductive work behavior, whereas job resources have a negative impact. Additionally, cognitive, emotional, and behavioral engagement each negatively affect counterproductive work behavior. Finally, platform formalization moderates the negative influence of gig workers' cognitive, emotional, and behavioral engagement on counterproductive work behavior. This research provides a comprehensive theoretical framework for digital gig platform managers to understand and predict gig workers' counterproductive work behavior. It also offers a solid theoretical basis for optimizing the work environment, enhancing job engagement, and mitigating counterproductive work behavior, thus fostering mutual development between gig workers and the platform.